Case Report: Management in a 25-year-old with Severe Erosive Vulvovaginal Lichen Planus [6R]. (May 2018) - Syed, Fatima; Vyas, Anuja
Abstract : INTRODUCTION: Erosive lichen planus (ELP) is a rare inflammatory dermatologic condition characterized by scarring and adhesions. ELP can involve female genitalia causing vulvar anatomic distortion and vaginal stenosis. Topical corticosteroids or calcineurin inhibitors are the mainstay of medical therapy. Vaginal adhesions and scarring can be managed with intravaginal steroids, dilators and surgical release. METHODS: Chart review; Literature review RESULTS: We present a 25-year-old Caucasian G0 with oral-vulvo-vaginal ELP. At time of presentation she had severe vaginal adhesive disease and was unable to have intercourse. The patient underwent surgical genital lysis of adhesions after which she was able to conceive and deliver a term neonate. Patient maintained vaginal patency in the puerperal period with topical corticosteroids, intravaginal corticosteroids and dilators. CONCLUSION: With aggressive surgical and medical management and continued close surveillance, patients with ELP affecting the vulva and vagina can have significantly improved quality of life and successfully deliver term pregnancies.